Dissolution rates during the early hydration of tricalcium silicate. (June 2015) - Bellmann, Frank; Sowoidnich, Thomas; Ludwig, Horst-Michael; Damidot, Denis
Abstract: The hydration of triclinic tricalcium silicate containing foreign oxides was investigated in this study. Two water/solid-ratios of 50 and 0.50 were applied. The kinetics of the reaction was analyzed by a combination of methods including thermal analysis, pore solution analysis, and calorimetry. From these data, the evolution of the rate of reaction during hydration was calculated. The results were compared to the free, unconstrained dissolution of tricalcium silicate in undersaturated solutions. Such dissolution rates were analyzed in a dissolution cell connected to an ICP-OES instrument. A comparison of the free dissolution rate in the absence of precipitation of hydrates to the rate of reaction showed that the dissolution of tricalcium silicate is much faster than the rate of reaction of the global process. Highlights: The kinetics of tricalcium silicate hydration was investigated in this study. The hydration was monitored by TG, pore solution analysis and calorimetry. Dissolution rates of tricalcium silicate were analyzed in undersaturated condition. During the first hours, dissolution rates were much higher than rates of reaction.